2024
DOI: 10.1109/tase.2023.3292029
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Control Platform and Architecture for the Integration of Wind-Hydrogen Systems Into the Grid

Abstract: Hydrogen is a promising energy vector for achieving renewable integration into the grid, thus fostering the decarbonization of the energy sector. This paper presents the control platform architecture of a real hydrogen-based energy production, storage, and re-electrification system (HESS) paired to a wind farm located in north Norway and connected to the main grid. The HESS consists of an electrolyser, a hydrogen tank, and a fuel cell. The control platform includes the management software, the control algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The datadriven energy management system was reported in Wen and Aziz 42 for the flexible operation of energy hubs and MCMGs, while hydrogen ammonia technologies were studied. Abdelghany et al 43,44 reported a new strategy according to the hierarchical rolling horizon control and model predictive control (MPC) to efficiently manage an HSS-based MG. Abdelghany et al 45 reported the control platform architecture of a real HSS-based energy system paired with WTs located in north Norway.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The datadriven energy management system was reported in Wen and Aziz 42 for the flexible operation of energy hubs and MCMGs, while hydrogen ammonia technologies were studied. Abdelghany et al 43,44 reported a new strategy according to the hierarchical rolling horizon control and model predictive control (MPC) to efficiently manage an HSS-based MG. Abdelghany et al 45 reported the control platform architecture of a real HSS-based energy system paired with WTs located in north Norway.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While these models exhibit a lower number of logical variables, they fail to capture crucial aspects such as device degradation. Moreover, other models in the literature, such as those in [54], [55], and [56], introduce two virtual states to represent the waiting actions, thus resulting in five-state automata. These models are characterized by a larger number of logical variables and inequalities: 5 state variables instead of 3, 20 transition variables instead of 6, and 115 linear inequalities instead of 40.…”
Section: B Comparison With Relevant Strategiesmentioning
confidence: 99%
“…To ensure highquality current in MG, it is crucial to design the LCL flter properly [9]. Te integration of wind-hydrogen systems into MGs is addressed in [10], with the emphasis placed on how energy fow management is conducted by advanced control strategies. Wind-hydrogen systems utilize excess wind power to electrolyze water, producing hydrogen for energy storage and use during periods of low wind availability [11].…”
Section: Introductionmentioning
confidence: 99%